Strategi Optimalisasi Pendapatan Pajak Daerah Untuk Meningkatkan Kemandirian Keuangan (Analisis di Kota Pekanbaru) - Kurniawan, Alek; Akbar, Bahrullah; Sinurat, Marja; Meltarini, Meltarini (Universitas Batanghari Jambi, 2024)
This research aims to analyze the contribution of local taxes to Local Own Source Revenue (PAD) and to identify the level of fiscal independence of the region in Pekanbaru City. The research method used is secondary data analysis from the realization data of local taxes and PAD from 2018 to 2022 obtained from the Pekanbaru City Revenue Agency. The data is then analyzed using descriptive statistical techniques to identify trends in the contribution of local taxes to PAD and the level of fiscal independence of the region during this period. The analysis results show that the contribution of local taxes to PAD in Pekanbaru City ranges from 80% to 93% during this period, with an increasing trend every year. However, fiscal independence of the region is still in the category of